Predictors and prevalence of social jet lag among King Saud employees and their families - Jumana Fatani; Reema Alnasser; Nouf Aljomah; Sarah Alhusaini; Ahmad Hersi (Wolters Kluwer Medknow Publications, 2020)
Background: Sleep is a crucial element in human beings' development and sustainment of a healthy lifestyle; any chronic misalignment between the sleep-wake cycles could be associated with numerous physical and mental disturbances. Social jet lag (SJL) is the discrepancy between the midpoints of sleep in workdays and free days. Up to date, there is a scarcity of studies conducted regarding this disorder in the Middle East. Hence, we aimed toward studying the prevalence and predictors of SJL. Methods: This was an observational cross-sectional study. The sample size was 328 participants who are King Saud University employees and their families. Saudi individuals aged 18 years and above were included in the study. Pregnant women were excluded from the study. Data were collected using an interview-administered questionnaire (Munich ChronoType Questionnaire). SJL was calculated as the absolute difference between the midpoints of sleep on free days and workdays. The association between SJL and predictors was assessed using the Chi-square test. Results: A sample of 226 females and 62 males were analyzed. SJL was categorized into three groups, which are <1 h, 1-2 h, and >2 h. Our results showed that SJL of >2 h represents approximately half of the participants (49.7%) and appeared to be more among the 18-33 years' age group (56.5%). Participants with >2 h were found to have a significant difference between sleep durations on work and free days (5.9 ± 1.8 vs. 8.67 ± 1.91 h, P < 0.001, respectively). Conclusion: Lower SJL hours are associated with factors such as increased age and similar sleep duration on work and free days, in addition to alarm use on free days. Whereas, younger age, inflexible work schedule, smoking, and soft drinks' consumption are linked with higher SJL hours. Our future aim is to increase the awareness of controlling the factors which lead to higher SJL hours and the importance of having a balanced sleep.